2021
DOI: 10.3390/plants10071440
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Gene-Based Markers for Girth Growth in Rubber Trees

Abstract: Girth growth is an important factor in both latex and timber production of the rubber tree. In this study, we performed candidate gene association mapping for girth growth in rubber trees using intron length polymorphism markers (ILP) in identifying the candidate genes responsible for girth growth. The COBL064_1 marker developed from the candidate gene (COBL4) regulating cellulose deposition and oriented cell expansion in the plant cell wall showed the strongest association with girth growth across two seasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…This approach has appealing features, including reducing the substantial multiple testing penalties required for GWAS and directly connecting statistical testing with functional biological units [ 23 , 24 ]. Several studies have successfully identified associations between SNPs in candidate genes and phenotypic traits in plants such as sugarcane [ 25 ], rubber tree [ 26 ], wheat [ 27 ], and ryegrass [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has appealing features, including reducing the substantial multiple testing penalties required for GWAS and directly connecting statistical testing with functional biological units [ 23 , 24 ]. Several studies have successfully identified associations between SNPs in candidate genes and phenotypic traits in plants such as sugarcane [ 25 ], rubber tree [ 26 ], wheat [ 27 ], and ryegrass [ 28 ].…”
Section: Introductionmentioning
confidence: 99%